2007
DOI: 10.1021/jo701549h
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Solvent (MeCN vs H2O) Decides Rate-Limiting Step in SNAr Aminolysis of 1-Fluoro-2,4-dinitrobenzene with Secondary Amines:  Importance of Brønsted-Type Analysis in Acetonitrile

Abstract: A kinetic study is reported for nucleophilic substitution reactions of 2,4-dinitro-1-fluorobenzene (DNFB) with a series of secondary amines in MeCN and H2O at 25.0 degrees C. The reaction in MeCN results in an upward curvature in the plot of k(obsd) vs [amine], indicating that the reaction proceeds through a rate-limiting proton transfer (RLPT) mechanism. On the contrary, the corresponding plot for the reaction in H2O is linear, implying that general base catalysis is absent. The ratios of the microscopic rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 57 publications
8
88
1
Order By: Relevance
“…The decomposition step is a bit more involved compared to the case of anionic nucleophiles, since the system formally loses a proton in addition to F − . A number of competitive decomposition processes have been postulated; expulsion of F − followed by deprotonation, 29 base-catalyzed deprotonation followed by loss of F − , 29,34 and the expulsion of HF in a concerted manner. 35 Which step in the reaction mechanism that is rate-determining is largly dependent upon the solvent.…”
Section: Neutral Nucleophiles and Hf As Leaving Groupmentioning
confidence: 99%
“…The decomposition step is a bit more involved compared to the case of anionic nucleophiles, since the system formally loses a proton in addition to F − . A number of competitive decomposition processes have been postulated; expulsion of F − followed by deprotonation, 29 base-catalyzed deprotonation followed by loss of F − , 29,34 and the expulsion of HF in a concerted manner. 35 Which step in the reaction mechanism that is rate-determining is largly dependent upon the solvent.…”
Section: Neutral Nucleophiles and Hf As Leaving Groupmentioning
confidence: 99%
“…In the case of attack of anionic nucleophiles (such as MeO − ) on fluorinated aromatics, the intermediate σ-complex is anionic and the leaving group is F − , whereas in the case of neutral nucleophiles (such as NH 3 ) the intermediate σ-complex is zwitterionic and the leaving group is HF. The departure of H and F can proceed along different mechanisms [79]. …”
Section: Introductionmentioning
confidence: 99%
“…Rate constant for these reactions in water was less than the other solvents. It was clearly observed that the rate constants for the reaction in DES was in a good agreement with the acetonitrile and water , …”
Section: Resultsmentioning
confidence: 66%